Strategy to Increase Customerâ€™s Purchase Intention on Garuda Indonesiaâ€™s International Flights Based on Brand Equity Factors - Muslim, Erlinda; QurÃ¢â‚¬â„¢anis, Ritsah (Jurnal Manajemen Teknologi, 2017)
Abstract. Garuda Indonesia has become one of the strongest airline brand in the world. However, with the very intense competition between competitors in international flights airlines, brand has an important role in customer's purchase intention. Therefore, Garuda Indonesia needs a strong brand equity strategy to increase customers' purchase intention for its international flights. To create such strategy, this research examines the impact of Customer Based Brand Equity (CBBE) factors on customer's Purchase Intention. Importance-Performance Analysis method is also used to obtain action items along with the execution priority of each action items. The research outcome can become a brand equity strategy for Garuda Indonesia in increasing customers' purchase intention, so that they can compete with other international airlines' brand that operates in Indonesia.Keywords: Brand equity, customer based brand equity, importance-performance analysis, purchase intention, structural equation modelingAbstrak. Garuda Indonesia merupakan salah satu maskapai penerbangan dengan merek yang kuat di dunia. Namun, dengan kompetisi yang semakin ketat antar maskapai penerbangan internasional, peran merek sangat berpengaruh terhadap niat beli pelanggan. Maka dari itu, Garuda Indonesia membutuhkan strategi ekuitas merek yang kuat untuk meningkatkan Purchase Intention pelanggan untuk penerbangan internasional. Dalam pembuatan strategi tersebut, diteliti pengaruh faktor-faktor Customer Based Brand Equity (CBBE) terhadap Purchase Intention pelanggan. Selain itu, digunakan Importance-Performance Analysis untuk mendapatkan action items beserta prioritas pelaksanaan untuk setiap action items. Hasil penelitian ini merupakan strategi ekuitas merek bagi Garuda Indonesia guna meningkatkan Purchase Intention pelanggan, sehingga dapat bersaing dengan merek maskapai penerbangan internasional lainnya yang beroperasi di Indonesia.Kata kunci: Customer based brand equity, ekuitas merek, purchase intention, structural equation modeling, importance-performance analysis